GSDMD is associated with survival in human breast cancer but does not impact anti-tumor immunity in a mouse breast cancer model - Boersma, Bart; Puddinu, Viola; Huard, Arnaud; Fauteux-Daniel, Sébastien; Wirapati, Pratyaksha; Guedri, Sofia; Tille, Jean-Christophe; McKee, Thomas; Pittet, Mikael; Palmer, Gaby; Bourquin, Carole (Frontiers in Immunology, 2024)
Inflammation plays a pivotal role in cancer development, with chronic inflammation promoting tumor progression and treatment resistance, whereas acute inflammatory responses contribute to protective anti-tumor immunity. Gasdermin D (GSDMD) mediates the release of pro-inflammatory cytokines such as IL-1β. While the release of IL-1β is directly linked to the progression of several types of cancers, the role of GSDMD in cancer is less clear. In this study, we show that GSDMD expression is upregulated in human breast, kidney, liver, and prostate cancer. Higher GSDMD expression correlated with increased survival in primary breast invasive carcinoma (BRCA), but not in liver hepatocellular carcinoma (LIHC). In BRCA, but not in LIHC, high GSDMD expression correlated with a myeloid cell signature associated with improved prognosis. To further investigate the role of GSDMD in anticancer immunity, we induced breast cancer and hepatoma tumors in GSDMD-deficient mice. Contrary to our expectations, GSDMD deficiency had no effect on tumor growth, immune cell infiltration, or cytokine expression in the tumor microenvironment, except for Cxcl10 upregulation in hepatoma tumors. In vitro and in vivo innate immune activation with TLR ligands, that prime inflammatory responses, revealed no significant difference between GSDMD-deficient and wild-type mice. These results suggest that the impact of GSDMD on anticancer immunity is dependent on the tumor type. They underscore the complex role of inflammatory pathways in cancer, emphasizing the need for further exploration into the multifaceted effects of GSDMD in various tumor microenvironments. As several pharmacological modulators of GSDMD are available, this may lead to novel strategies for combination therapy in cancer.